The long-term decline in surface velocity of Greenland’s land-terminating outlet glaciers – an ice-sheet-wide phenomenon? - Morton, Hamish (The University of Edinburgh, 2018)
The Greenland Ice Sheet has the potential to contribute ~7 m to global mean sea level (Morlighem et al., 2017). Ice sheet velocities influence rates of ice transport to the ablation zone and therefore impact rates of mass loss and contribution to sea level rise (Zwally et al., 2002). A recent study found that a land-terminating region of the Greenland Ice Sheet experienced a ~12% reduction in velocity between 1985 and 2014 (Tedstone et al., 2015). This was attributed to increasing antecedent runoff production leading to the development of efficient drainage systems, progressively reducing basal water pressure and therefore sliding (Tedstone et al., 2015). Until now, only velocities of a land-terminating region in the southwest have been examined. Furthermore, it has recently been argued that less deceleration has occurred than initially observed (Joughin et al., 2018a). In this paper, the entire Landsat archive from 1985 to 2016 is exploited using feature tracking techniques, to examine velocities of a land-terminating region located on Greenland’s central west coast. Prior to and following the feature tracking process, data are manipulated using several different techniques to enhance outputs of final velocity maps, allowing a complete time series to be constructed. A feat that would not otherwise be possible. It is found that although deceleration is less than that observed in the southwest, antecedent runoff production still explains up to 59% of change. In replicating the findings of past studies, it is concluded that measured deceleration is not a product of sampling issues.